PEREMPUAN DAN PEMBERDAYAAN POTENSI LINGKUNGAN MELALUI KEMAMPUAN KEAKSARAAN DI KAMPUNG SOBA KABUPATEN MAPPI PROVINSI PAPUA - Aisyah Ali; Sudaryana Sudaryana; Catur F. Djarwo (JURNAL PENGABDIAN PAPUA, 2020)
Papua Province is in the first position for the number of illiterates. The number of illiterate people in the two districts in the Southern region of  Papua, namely Mappi Regency and Asmat Regency, is still very high, reaching 60%. Women have greater illiteracy rates than men. The Ministry of  Education and Culture notes that there are 1,157,703 men who are still illiterate. While the number of  illiterate women reached 2,258,990. Entering this information era,  literacy is an important key to improving education, health, nutrition and family welfare. Because with literacy and education, women will be more empowered, can make their own decisions and have a strong bargaining position in the family and community. Considering women as the most influential people in a group, with family as an example, women are the main focus in this matter. This activity is called Kuliah Kerja Nyata Pembelajaran Pemberdayaan Masyarakat (KKN PPM). It is a University Student Community Service which focus on Community Empowerment as the Learning Process/Activities. This takes place from July 26 to August 26, 2019, in Soba Village, Obaa District, Mappi Regency, Papua Province. Activities that involve students of Elementary School Teacher Education Study Program of the  Faculty of Teacher Training and Education of Cenderawasih University are  literacy learning activities (read, write and count) with women as the target of the activities. The method used in this activity is counseling, interactive discussion and community learning assistance. The implementation of KKN-PPM activities was enthusiastically welcomed by the Government of Mappi Regency and also all the village officials and the local community. The target community, who are generally women, take part  in the literacy program very enthusiastically. The implementation of literacy activities was facilitated by the Principal and Teachers of YPPK St. Paulus Elementary School in Soba Village, Obaa District, Mappi Regency. Keywords: Literacy ability, Empowerment of Environmental Potential,counseling